Neodymium-iron-boron magnet and method for producing same

CN123017664APending Publication Date: 2026-10-30YUYAO HONGWEI MAGNETIC MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611342869.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为了改善钆在烧结过程中大量进入主相晶格,会严重稀释主相磁矩,导致剩磁大幅下降的问题,本申请提供一种钕铁硼磁材及其制备方法,通过双合金组分拆分、晶界润湿元素配比优化以及有机表面配位调控体系的协同作用,实现钆元素的晶界定向富集

Benefits of technology

1、本申请通过采用合金A为主相基体、合金B为晶界调控合金的双合金设计,将钆、镝等重稀土元素集中配置于合金B中,使其在烧结过程中主要随液相晶界相分布于晶粒边界区域,减少了钆元素进入主相晶格对磁矩的稀释,从而在保持磁体高剩磁的同时,借助镝元素较强的各向异性场有效提升了矫顽力;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to a neodymium-iron-boron magnet and a preparation method thereof, and relates to the technical field of neodymium-iron-boron magnets. The neodymium-iron-boron magnet comprises alloy A and alloy B. The alloy A comprises the following components in parts by weight: praseodymium-neodymium 29.1-31.5 parts, boron 0.98-1.06 parts, cobalt 0.43-0.68 parts and iron 61-65 parts. The alloy B comprises the following components in parts by weight: praseodymium-neodymium 0.9-1 part, gadolinium 0.6-1 part, dysprosium 0.5-0.8 part, cobalt 0.07-0.12 part, copper 0.1-0.15 part, gallium 0.05-0.1 part and iron 2-3 parts. According to the double-alloy design that the alloy A is used as a main phase matrix and the alloy B is used as a grain boundary control alloy, the heavy rare earth elements such as gadolinium and dysprosium are concentrated in the alloy B, so that the heavy rare earth elements mainly distribute in the grain boundary region along the liquid phase grain boundary phase in the sintering process, the dilution of the magnetic moment caused by the gadolinium element entering the main phase crystal lattice is reduced, and the high remanence of the magnet is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of neodymium iron boron magnet technology, specifically to a neodymium iron boron magnet and its preparation method. Background Technology

[0002] Neodymium iron boron permanent magnets have significant advantages such as high remanence, high coercivity and high energy product, and are widely used in new energy vehicles, wind power generation, energy-saving home appliances, consumer electronics and aerospace, etc. They are key basic materials supporting the development of modern industry and new energy industry.

[0003] With the increasing demands for high-temperature stability in downstream applications, introducing heavy rare earth elements into NdFeB formulations to improve coercivity has become a common practice in the industry. Among related technologies, dysprosium and terbium are the mainstream choices for improving coercivity due to their high magnetocrystalline anisotropy, but their scarcity and high price significantly increase magnet manufacturing costs. Gadolinium, as a relatively inexpensive heavy rare earth element, has a high Curie temperature and can theoretically improve the thermal stability of magnets. Therefore, some formulations attempt to partially replace dysprosium with gadolinium to reduce costs.

[0004] However, gadolinium's magnetocrystalline anisotropy field is significantly lower than that of praseodymium and neodymium. If gadolinium enters the main phase lattice in large quantities during sintering, it will severely dilute the main phase magnetic moment, leading to a significant decrease in remanence. Furthermore, its efficiency in improving coercivity is far lower than that of dysprosium and terbium. Therefore, how to effectively suppress gadolinium diffusion into the main phase lattice and promote its uniform enrichment in the grain boundary region while retaining gadolinium and controlling raw material costs is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] To address the problem that excessive gadolinium entry into the main phase lattice during sintering severely dilutes the main phase magnetic moment, leading to a significant decrease in remanence, this application provides a neodymium iron boron magnet and its preparation method. Through the synergistic effect of dual alloy component separation, grain boundary wetting element ratio optimization, and organic surface coordination regulation system, the grain boundary directional enrichment of gadolinium is achieved.

[0006] In a first aspect, this application provides a neodymium iron boron magnetic material, which adopts the following technical solution: A neodymium iron boron magnet is prepared from alloy A and alloy B. The raw materials for preparing alloy A include the following components in parts by weight: 29.1-31.5 parts of praseodymium and neodymium, 0.98-1.06 parts of boron, 0.43-0.68 parts of cobalt, and 61-65 parts of iron. The raw materials for preparing alloy B include the following components in parts by weight: 0.9-1 parts of praseodymium and neodymium, 0.6-1 parts of gadolinium, 0.5-0.8 parts of dysprosium, 0.07-0.12 parts of cobalt, 0.1-0.15 parts of copper, 0.05-0.1 parts of gallium, and 2-3 parts of iron.

[0007] By adopting the above technical solution, alloy A is the main phase matrix, which plays a core role in providing the basic magnetic moment and ensuring remanence. Placing praseodymium, neodymium, boron, iron, and cobalt in alloy A is beneficial for obtaining microcrystalline ribbons with uniform grains and a high proportion of the main phase, and reduces the interference of gadolinium on the crystallization process of the main phase. Alloy B is a rare earth-rich, low-melting-point grain boundary control alloy. Gadolinium, dysprosium, copper, gallium, and other elements are concentrated in this alloy, so that gadolinium is in the grain boundary phase system from the raw material stage. During sintering, it is mainly distributed in the grain boundary region along with the liquid phase grain boundary phase, which greatly reduces the driving force for gadolinium to diffuse into the main phase lattice. Moreover, retaining a small amount of praseodymium, neodymium, cobalt, and iron in alloy B helps to lower the melting point of the grain boundary alloy and improve its wettability to the main phase grains, thereby preparing neodymium iron boron magnets with high remanence and coercivity.

[0008] Preferably, the total mass ratio of copper and gallium to gadolinium is (0.2-0.3):1.

[0009] By adopting the above technical solution, the magnetocrystalline anisotropy field of gadolinium itself is relatively weak. If gadolinium enters the main phase lattice during sintering, it will partially replace praseodymium and neodymium, dilute the magnetic moment of the main phase, and cause the remanence of the magnet to decrease. If gadolinium locally agglomerates at the grain boundary, it is difficult to form a continuous and uniform gadolinium-rich grain boundary phase, which provides a uniformly distributed grain boundary carrier for dysprosium.

[0010] Copper and gallium, as low-melting-point components, when their total mass ratio to gadolinium is controlled within the aforementioned range, help to construct a grain boundary liquid phase with suitable viscosity. This promotes the uniform spread of gadolinium in the grain boundary region, reduces the risk of gadolinium entering the main phase, and forms a continuously distributed gadolinium-rich grain boundary layer. This provides a good distribution carrier for the segregation of dysprosium at the grain boundary-main phase interface, thereby promoting the uniform enrichment of dysprosium in the grain boundary region and effectively enhancing coercivity by leveraging the strong anisotropic field of dysprosium.

[0011] Preferably, it further includes a regulator A, which includes at least one of ammonium citrate and ammonium tartrate.

[0012] By adopting the above technical solution, the hydroxy polycarboxylic acid ammonium salt molecule has multiple carboxyl groups and ortho-hydroxy groups in its molecular structure, which can form stable coordination complexes with rare earth ions. During the sintering heating process, it plays a certain role in regulating the migration behavior of grain boundary control elements such as gadolinium and dysprosium, which helps these elements to accumulate in the grain boundary region rather than enter the main phase lattice in large quantities. On the other hand, the ammonium salt form does not introduce alkali metal impurities, avoiding the risk of alkali metals destroying the grain boundary phase structure. Thus, the gadolinium-dysprosium composite grain boundary control system can play a more effective role in the grain boundary region and improve the coercivity of the magnet.

[0013] Preferably, the regulator A is an ammonium citrate salt, which includes at least one of triammonium citrate and diammonium hydrogen citrate.

[0014] By adopting the above technical solution, ammonium citrate molecules have more coordination sites, which strengthens the complexation ability of rare earth ions and has a more significant effect on the migration regulation of the gadolinium-dysprosium composite grain boundary regulation system. Moreover, the pH values ​​of triammonium citrate and diammonium hydrogen citrate are close to neutral, which has a mild acid etching effect on the surface of magnetic powder, ensuring the integrity of the surface layer of magnetic powder particles and reducing the risk of rare earth oxidation and magnetic powder activity reduction caused by surface acid etching, thus taking into account both high remanence and high coercivity.

[0015] Preferably, it also includes a regulator B, wherein the regulator B is anhydrous glucose.

[0016] Preferably, the mass ratio of regulator A to regulator B is (1.5-4):1.

[0017] By adopting the above technical solution, glucose molecules contain aldehyde groups, which have a certain reducing property. During its thermal decomposition, it helps to reduce the local oxygen partial pressure of magnetic powder particles. After high-temperature sintering and decomposition, glucose is partially carbonized to form an amorphous carbon layer, which is uniformly distributed at the original particle boundary, playing a physical barrier role, further hindering the diffusion of gadolinium into the main phase grain and hindering the excessive growth of the main phase grain.

[0018] When anhydrous glucose is used in combination with regulator A, the two substances melt sequentially to form a homogeneous eutectic liquid phase. Regulator A provides strongly chelating carboxyl sites, while anhydrous glucose provides multiple ortho-hydroxyl groups for coordination, resulting in multiple adsorption and further strengthening the surface anchoring of rare earth elements. Furthermore, during the decomposition stage, the trace amounts of ammonia released from regulator A may undergo a weak Maillard reaction with the aldehyde groups of glucose, generating a small amount of nitrogen-containing oligomers. This moderately improves the thermal stability of the organic system, thereby prolonging the duration of the regulator's action and making the segregated layer of dysprosium at the grain boundary-main phase interface more continuous and complete, further enhancing the magnet's coercivity.

[0019] Secondly, this application provides a method for preparing neodymium iron boron magnets, which adopts the following technical solution: A method for preparing neodymium iron boron magnets, comprising the following steps: Molten strip casting: According to the formula of alloy A, praseodymium, neodymium, boron, cobalt and iron are weighed and smelted. The resulting molten liquid is then cast to obtain strip A. According to the formula of alloy B, praseodymium, neodymium, gadolinium, dysprosium, cobalt, copper, gallium and iron are weighed and smelted. The resulting molten liquid is then spun into a strip to obtain strip B. Hydrogen-crushed grinding: The belt spinning plate A and belt spinning plate B are hydrogen-crushed into coarse powder A and coarse powder B, respectively. After premixing, coarse powder A and coarse powder B are ground together by an air jet mill to obtain magnetic powder. Mixed pressing: The magnetic powder is placed under nitrogen protection and molded to obtain a pressed blank; Sintering and tempering: The pressed blank is sintered and then subjected to a two-stage tempering heat treatment to obtain neodymium iron boron magnets.

[0020] Preferably, after air jet milling, the regulator A and / or regulator B are dispersed in an alcohol solvent, and magnetic powder is added by spraying and mixed evenly to obtain mixed magnetic powder; the mixed magnetic powder is placed under nitrogen protection for molding to obtain a compact.

[0021] By adopting the above technical solution, the regulator is added by spraying alcohol solvent after air jet milling and before pressing, which avoids the damage to organic matter caused by high temperature or strong mechanical action in the melting and hydrogen breaking stages. This allows the regulator to be uniformly coated on the surface of magnetic powder particles and to act precisely on the grain boundary formation region in the subsequent sintering process. In addition, the addition of the regulator by dispersing it with alcohol solvent effectively improves the uniformity of the regulator coating.

[0022] Preferably, the sintering process includes the following stages: First stage: Increase the temperature to 180-210℃ at a rate of 4-6℃ / min, and hold for 20-40 min; Second stage: Increase the temperature to 380-420℃ at a rate of 2-3℃ / min, and hold for 50-70 min; Third stage: Increase the temperature to 1050-1100℃ at a rate of 4-6℃ / min and hold for 2-3 hours.

[0023] By adopting the above technical solution, regulator A and regulator B melt in the first stage, and the eutectic liquid phase formed during the heat preservation process is fully spread on the surface of the magnetic powder particles; the slow heating and long heat preservation in the second stage are conducive to the orderly decomposition of nitrogen-containing oligomers generated by the reaction of organic matter and the partial carbonization products of glucose, and the decomposition products are gradually discharged in the form of gas phase, reducing the risk of cracking of the compact caused by the generation of a large amount of gas by violent reaction; the third stage is the conventional sintering interval for magnet densification, where the gadolinium-dysprosium composite system fixed on the particle surface is uniformly distributed in the final grain boundary region along with the grain boundary liquid phase, achieving an effective improvement in coercivity, and the main phase volume is fully preserved, maintaining a high remanence level.

[0024] Preferably, the secondary tempering includes: First stage tempering: Hold at 880-950℃ for 1.5-2.5 hours; Second stage tempering: Hold at 480-550℃ for 2.5-3.5 hours.

[0025] By adopting the above technical solution, the first-stage tempering is located in the melting or semi-melting range of the rare-earth-rich grain boundary phase, which causes morphological reconstruction of the grain boundary phase. This optimizes the coating state of the grain boundary phase with the main phase grains, reduces the magnetic coupling between the main phase grains, and promotes a more continuous and complete segregation layer of dysprosium at the grain boundary-main phase interface, thereby improving the coercivity of the magnet and improving the squareness of the demagnetization curve. The second-stage tempering promotes the further precipitation and purification of the grain boundary interface by trace amounts of harmful impurities that may exist in the grain boundary (such as trace amounts of carbon and nitrogen impurities remaining after the decomposition of regulators A / B), reduces the demagnetization nucleation rate, and stabilizes the microstructure of the gadolinium-dysprosium-rich grain boundary phase. The second-stage tempering further completes the shaping of the grain boundary regulation system, enabling the magnet to obtain higher coercivity and thermal stability while maintaining high remanence.

[0026] In summary, this application has the following beneficial effects: 1. This application adopts a dual-alloy design with alloy A as the main phase matrix and alloy B as the grain boundary control alloy. Heavy rare earth elements such as gadolinium and dysprosium are concentrated in alloy B, so that they are mainly distributed in the grain boundary region along with the liquid phase grain boundary phase during sintering. This reduces the dilution of magnetic moment by gadolinium entering the main phase lattice. Thus, while maintaining the high remanence of the magnet, the coercivity is effectively improved by the strong anisotropic field of dysprosium. 2. This application constructs a grain boundary liquid phase with suitable viscosity by controlling the total mass ratio of copper and gallium to gadolinium, which promotes the uniform spread of gadolinium in the grain boundary region and provides a good distribution carrier for the segregation of dysprosium at the grain boundary-main phase interface. 3. This application uses the combination and synergy of regulator A and regulator B to coordinate and anchor the gadolinium-dysprosium composite grain boundary control system and regulate its migration, thereby promoting the formation of a continuous and complete segregated layer of dysprosium at the grain boundary-main phase interface, which improves the coercivity and thermal stability of the magnet. Detailed Implementation

[0027] The raw materials in this application include the following: Ammonium citrate salts: The following explanation uses triammonium citrate and diammonium hydrogen citrate as examples. Triammonium citrate: Use commercially available product with CAS number 3458-72-8; Diammonium hydrogen citrate: Uses commercially available products with CAS number 3012-65-5; Ammonium tartrate salts: Taking ammonium hydrogen tartrate as an example, the commercially available product with CAS number 3095-65-6 is used; Anhydrous glucose: Commercially available product with CAS number 50-99-7 is used; The present application will be further described in detail below with reference to embodiments and comparative examples. Example

[0028] A method for preparing neodymium iron boron magnets includes the following steps: Melting and spinning: Weigh 3000g of praseodymium and neodymium, 102g of boron, 55g of cobalt and 6300g of iron and put them into a vacuum induction melting furnace and heat them to 1480℃ for melting. Spin the resulting molten liquid to obtain spinning sheet A. Weigh 95g of praseodymium and neodymium, 80g of gadolinium, 65g of dysprosium, 9g of cobalt, 12.5g of copper, 7.5g of gallium and 275g of iron and put them into a vacuum induction melting furnace and heat them to 1220℃ for melting. The resulting molten liquid is then spun into a strip to obtain strip B. Hydrogen-driven grinding: The belt spinning blades A and B are hydrogen-driven to produce coarse powder A and coarse powder B, respectively. After premixing, coarse powder A and coarse powder B are ground together by an air jet mill to obtain magnetic powder. The average particle size of the magnetic powder is 3.5 μm (the average particle size can be between 3-4 μm). Hybrid pressing: Magnetic powder is placed under nitrogen protection and molded to obtain a pressed blank; Sintering and tempering: The pressed blank is sintered and then subjected to a two-stage tempering heat treatment; The sintering process includes: First stage: Increase the temperature to 195℃ at a rate of 5℃ / min and hold for 30 min; Second stage: Increase the temperature to 400℃ at 3℃ / min and hold for 60 min; Third stage: Increase the temperature to 1080℃ at a rate of 5℃ / min and hold for 3 hours; Secondary tempering includes: First stage tempering: hold at 900℃ for 2 hours, then rapidly cool; Second-stage tempering: Hold at 500℃ for 3 hours, then cool to room temperature with the furnace; This yields neodymium iron boron magnets.

[0029] Example 2-3 Examples 2-3 are based on the preparation method of Example 1, but the amounts of each component of alloy A and alloy B are adjusted, as shown in Table 1.

[0030] Comparative Example 1 Comparative Example 1: Based on the preparation method of Example 1, 3095g of praseodymium-neodymium, 102g of boron, 64g of cobalt, 80g of gadolinium, 65g of dysprosium, 12.5g of copper, 7.5g of gallium, and 6575g of iron were added together into a vacuum induction melting furnace and heated to 1480°C for melting. The resulting molten liquid was then spun into a strip to obtain a spun strip sheet. Subsequently, the spun strip sheet was subjected to hydrogen-induced grinding, with the other conditions remaining unchanged.

[0031] The neodymium iron boron magnets prepared in Examples 1-3 and Comparative Example 1 were subjected to the following performance tests, and the test results are shown in Table 1: Remanence and intrinsic coercivity According to GB / T 3217-2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnet) Materials", the remanence (Br) and intrinsic coercivity (Hcj) of neodymium iron boron magnets were tested.

[0032] Table 1. Raw material list and performance test table for Examples 1-3 and Comparative Example 1

[0033] Referring to Table 1, a comparison of Examples 1-3 and Comparative Example 1 shows that the magnetic properties of the NdFeB magnets prepared in Examples 1-3 are superior to those in Comparative Example 1. This is because Comparative Example 1 uses a single alloy process, where gadolinium and dysprosium are randomly distributed in the main alloy. During sintering, gadolinium enters the main phase lattice, diluting the magnetic moment, and the grain boundary distribution is uneven. In contrast, Examples 1-3 use a dual alloy process, concentrating gadolinium and dysprosium in the grain boundary control alloy, reducing the probability of heavy rare earth elements entering the main phase, while ensuring the uniform distribution of the grain boundary phase.

[0034] In comparison, the neodymium iron boron magnet of Example 1 has better magnetic properties, therefore Example 1 is preferred.

[0035] Examples 4-7 Examples 4-7 are based on the preparation method of Example 1, with the mass ratio of copper to gallium maintained at 5:3 and the total mass of copper, gallium and gadolinium at 100g. The total mass of copper and gallium and the mass ratio of gadolinium are adjusted as shown in Table 2.

[0036] The neodymium iron boron magnets prepared in Examples 4-7 were subjected to the above performance testing tests, and the test results are shown in Table 2.

[0037] Table 2. Total mass ratio of copper and gallium to gadolinium in Examples 1 and 4-7, and performance test results.

[0038] Referring to Table 2, a comparison of Examples 1 and 4-7 shows that when the total mass ratio of copper and gallium to gadolinium is in the range of (0.2-0.3):1, the prepared NdFeB magnet exhibits superior magnetic properties. This is because, within this range, copper and gallium, as low-melting-point components, help to construct a grain boundary liquid phase with suitable viscosity, promoting the uniform spread of gadolinium in the grain boundary region, reducing its risk of entering the main phase, and forming a continuously distributed gadolinium-rich grain boundary layer. This provides a good distribution carrier for the segregation of dysprosium at the grain boundary-main phase interface, thereby promoting the uniform enrichment of dysprosium in the grain boundary region and effectively enhancing coercivity through the strong anisotropic field of dysprosium.

[0039] Examples 8-10 Example 8 is based on the preparation method of Example 1, in which the magnetic powder is transferred to a powder mixer after being ground in an air jet mill; Disperse 0.715 g of triammonium citrate in 20 mL of anhydrous ethanol and sonicate until a homogeneous suspension is formed. The mixing machine was set to 18 rpm, and the triammonium citrate ethanol suspension was sprayed in at a rate of 0.5 mL / min under continuous stirring. After spraying, continue mixing for 60 minutes while maintaining the rotation speed and the jacket temperature at 50°C to allow the anhydrous ethanol to evaporate and obtain mixed magnetic powder. The mixed magnetic powder was molded under nitrogen protection to obtain a compact, with all other conditions remaining unchanged.

[0040] Example 9 is based on the preparation method of Example 8, except that triammonium citrate is replaced with diammonium hydrogen citrate in equal amounts, while the other conditions remain unchanged.

[0041] Example 10 is based on the preparation method of Example 8, except that triammonium citrate is replaced with an equal amount of ammonium hydrogen tartrate, while the other conditions remain unchanged.

[0042] The neodymium iron boron magnets prepared in Examples 8-10 were subjected to the above performance testing tests, and the test results are shown in Table 3.

[0043] Table 3 Performance test results for Examples 1 and 8-10

[0044] Referring to Table 3, a comparison between Example 1 and Examples 8-10 shows that the magnetic properties of the NdFeB magnets prepared in Examples 8-10 are all superior to those in Example 1. This indicates that triammonium citrate, diammonium hydrogen citrate, and ammonium hydrogen tartrate can all help regulate the migration behavior of grain boundary control elements such as gadolinium and dysprosium, inhibit their diffusion into the main phase lattice, reduce the dilution of the main phase magnetic moment, and increase the effective heavy rare earth content at the grain boundaries, while also improving the remanence and intrinsic coercivity of the NdFeB magnets.

[0045] In comparison, the neodymium iron boron magnet of Example 8 has better magnetic properties, therefore Example 8 is preferred.

[0046] Examples 11-15 Example 11 is based on the preparation method of Example 8, in which 0.285 g of anhydrous glucose and 0.715 g of triammonium citrate are dispersed together in 20 mL of anhydrous ethanol, and the other conditions remain unchanged.

[0047] Examples 12-15 are based on the preparation method of Example 11, with the total mass of triammonium citrate and anhydrous glucose kept at 1.000 g, and the mass ratio of triammonium citrate and anhydrous glucose is adjusted as shown in Table 4.

[0048] The neodymium iron boron magnets prepared in Examples 11-15 were subjected to the above performance testing tests, and the test results are shown in Table 4.

[0049] Table 4. Mass ratio of triammonium citrate and anhydrous glucose and performance test results in Examples 8 and 11-15.

[0050] Referring to Table 4, a comparison of Examples 8 and 11-15 shows that the magnetic properties of the NdFeB magnets prepared in Examples 11-15 are superior to those in Example 8. This is because the combination of anhydrous glucose and triammonium citrate further enhances the surface spreading and anchoring effect, and the reducing property of the aldehyde group of anhydrous glucose reduces the oxidation loss of rare earth elements on the surface. Some carbonization products can also form a temporary barrier in the early stage of sintering and prolong the regulation time, thereby further improving the effective enrichment of heavy rare earth elements at the grain boundary.

[0051] Comparing Examples 11-15, it can be seen that when the mass ratio of anhydrous glucose to triammonium citrate is in the range of (1.5-4):1, the prepared NdFeB magnets have better magnetic properties. This is because when the proportion of anhydrous glucose is too high, the amount of residual carbon after glucose decomposition increases, generating trace amounts of rare earth carbide impurities, which leads to a simultaneous decrease in remanence and coercivity. When the proportion of anhydrous glucose is too low, its antioxidant and temperature-delaying effects are weak, and the improvement effect is not obvious.

[0052] Examples 16-18 Example 16 is based on the preparation method of Example 11, but without the first stage of sintering treatment, the temperature is directly increased to 400°C at 3°C / min, and the other conditions remain unchanged.

[0053] Example 17 is based on the preparation method of Example 11, except that the temperature is increased at a rate of 5°C / min during the second stage of sintering, while the other conditions remain unchanged.

[0054] In Example 18, based on the preparation method of Example 11, the holding time at 400°C was shortened to 30 min during the second stage of sintering, while the other conditions remained unchanged.

[0055] The neodymium iron boron magnets prepared in Examples 16-18 were subjected to the above performance testing tests, and the test results are shown in Table 5.

[0056] Table 5 Performance test results for Examples 11 and 16-18

[0057] Referring to Table 5, a comparison of Examples 11 and 16-18 shows that the magnetic properties of the NdFeB magnets prepared in Example 11 are superior to those in Examples 16-18. This is because Example 16 did not undergo a first-stage low-temperature holding period, and the anhydrous glucose and triammonium citrate did not fully melt, spread, and complete coordination anchoring before entering the rapid decomposition stage, weakening the regulating effect of the regulator and resulting in a decrease in both remanence and coercivity. In Example 17, the second-stage heating rate was too fast, causing the organic matter to decompose and release gas in a short time, which may impact the compact structure and damage the integrity of part of the coating layer, resulting in a decrease in both remanence and coercivity. In Example 18, the second-stage holding time was too short, resulting in insufficient decomposition and removal of organic matter, a slight increase in residual carbon, and a slight decrease in coercivity.

[0058] Examples 19-21 Example 19 is based on the preparation method of Example 11, but without the second-stage tempering, and all other conditions remain the same.

[0059] Example 20 is based on the preparation method of Example 11, except that the temperature of the second-stage tempering is adjusted to 580°C, while the other conditions remain unchanged.

[0060] Example 21 is based on the preparation method of Example 11, except that the temperature of the second-stage tempering is adjusted to 450°C, while the other conditions remain unchanged.

[0061] The neodymium iron boron magnets prepared in Examples 19-21 were subjected to the above performance testing tests, and the test results are shown in Table 6.

[0062] Table 6 Performance test results for Examples 11 and 19-21

[0063] Referring to Table 6, a comparison of Examples 11 and 19-21 shows that the magnetic properties of the NdFeB magnets prepared in Example 11 are superior to those in Examples 19-21. This is because Example 19 did not undergo a second-stage tempering, and after the first-stage tempering, trace amounts of harmful impurities (such as trace amounts of carbon and nitrogen impurities generated by the decomposition of the regulator and local non-uniform phases formed during sintering) still remain in the grain boundaries. These impurities are difficult to fully precipitate, resulting in a decrease in remanence and coercivity. In Example 20, the second-stage tempering temperature was too high, which may cause coarsening and spheroidization of the gadolinium-dysprosium rich grain boundary structure, leading to a deterioration in the grain boundary's coating state on the main phase grains and an increase in demagnetization nucleation sites. In Example 21, the second-stage tempering temperature was too low, resulting in a weak driving force for the precipitation of trace harmful impurities in the grain boundaries, making it difficult to fully purify them. A small number of defects still exist at the grain boundary interface, leading to a slight decrease in coercivity.

[0064] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A neodymium iron boron magnetic material, characterized in that, The raw materials for preparation include alloy A and alloy B. The raw materials for preparing alloy A include the following components in parts by weight: praseodymium-neodymium 29.1-31.5 parts, boron 0.98-1.06 parts, cobalt 0.43-0.68 parts and iron 61-65 parts. The raw materials for preparing alloy B include the following components in parts by weight: 0.9-1 parts of praseodymium and neodymium, 0.6-1 parts of gadolinium, 0.5-0.8 parts of dysprosium, 0.07-0.12 parts of cobalt, 0.1-0.15 parts of copper, 0.05-0.1 parts of gallium, and 2-3 parts of iron.

2. The neodymium iron boron magnet according to claim 1, characterized in that: The total mass ratio of copper and gallium to gadolinium is (0.2-0.3):

1.

3. The neodymium iron boron magnet according to claim 1, characterized in that: It also includes regulator A, which comprises at least one of ammonium citrate and ammonium tartrate.

4. The neodymium iron boron magnet according to claim 3, characterized in that: The regulator A is an ammonium citrate salt, which includes at least one of triammonium citrate and diammonium hydrogen citrate.

5. The neodymium iron boron magnet according to claim 3, characterized in that: It also includes regulator B, which is anhydrous glucose.

6. The neodymium iron boron magnet according to claim 5, characterized in that: The mass ratio of regulator A to regulator B is (1.5-4):

1.

7. The method for preparing neodymium iron boron magnets according to any one of claims 1-6, characterized in that, Includes the following steps: Molten strip casting: According to the formula of alloy A, praseodymium, neodymium, boron, cobalt and iron are weighed and smelted. The resulting molten liquid is then cast to obtain strip A. According to the formula of alloy B, praseodymium, neodymium, gadolinium, dysprosium, cobalt, copper, gallium and iron are weighed and smelted. The resulting molten liquid is then spun into a strip to obtain strip B. Hydrogen-crushed grinding: The belt spinning plate A and belt spinning plate B are hydrogen-crushed into coarse powder A and coarse powder B, respectively. After premixing, coarse powder A and coarse powder B are ground together by an air jet mill to obtain magnetic powder. Mixed pressing: The magnetic powder is placed under nitrogen protection and molded to obtain a pressed blank; Sintering and tempering: The pressed blank is sintered and then subjected to a two-stage tempering heat treatment to obtain neodymium iron boron magnets.

8. The method for preparing neodymium iron boron magnets according to claim 7, characterized in that: After grinding in an air jet mill, the regulator A and / or regulator B are dispersed in an alcohol solvent, and magnetic powder is added by spraying and mixed evenly to obtain mixed magnetic powder; the mixed magnetic powder is placed under nitrogen protection for molding to obtain a compact.

9. The method for preparing neodymium iron boron magnets according to claim 7 or 8, characterized in that, The sintering process includes the following stages: First stage: Increase the temperature to 180-210℃ at a rate of 4-6℃ / min, and hold for 20-40 min; Second stage: Increase the temperature to 380-420℃ at a rate of 2-3℃ / min, and hold for 50-70 min; Third stage: Increase the temperature to 1050-1100℃ at a rate of 4-6℃ / min and hold for 2-3 hours.

10. The method for preparing neodymium iron boron magnets according to claim 7 or 8, characterized in that, The secondary tempering includes: First stage tempering: Hold at 880-950℃ for 1.5-2.5 hours; Second stage tempering: Hold at 480-550℃ for 2.5-3.5 hours.